Clustering of under-five mortality in the Navrongo HDSS in the Kassena-Nankana District of northern Ghana - Martin Adjuik; Ernest Kanyomse; Felix Kondayire; George Wak; Abraham Hodgson (Taylor & Francis Group, 2010)
Background: Under-five mortality is a major public health problem and one of the health indicators of health care in sub-Saharan Africa. In order to address inefficient health systems, there is a need to identify the spatial distribution of under-five mortality, especially areas of high mortality clustering. This study aimed to explore spatial and temporal clustering in under-five mortality in the Kassena-Nankana District of the Upper East region. Methods: We used data from the Navrongo Health and Demographic Surveillance System in the Kassena- Nankana District of northern Ghana, which had an average population of 140,000 of which about 18,400 were under five years of age. We analysed under-five mortality in 49 villages during the period 1997–2006. We calculated total under-five mortality rates and investigated their geographical distributions. A spatial scan statistic was used to test for clustering of the mortality in both space and time. Results: Under-five mortality has been declining during the period. However, the data show a persistently higher than average clustering of mortality over the period among villages mainly in the north-eastern parts of the district. Conclusion: There is a higher than average under-five mortality clustering in the villages in the north-east of the district and this may suggest a relatively poor health care system despite the many health interventions that took place over time in the district, including the Community Health and Family Planning Project, whose impact may not have been felt in these parts of the district between 1995 and 2004.